Aptamer-targeted inhibition of mTOR in T cells enhances antitumor immunity - Alexey Berezhnoy; Iris Castro; Agata Levay; Thomas R. Malek; Eli Gilboa (The Journal of Clinical Investigation, 2014)
Recent studies have underscored the importance of memory T cells in mediating protective immunity against pathogens and cancer. Pharmacological inhibition of regulators that mediate T cell differentiation promotes the differentiation of activated CD8+ T cells into memory cells. Nonetheless, pharmacological agents have broad targets and can induce undesirable immunosuppressive effects. Here, we tested the hypothesis that aptamer-targeted siRNA inhibition of mTOR complex 1 (mTORC1) function in CD8+ T cells can enhance their differentiation into memory T cells and potentiate antitumor immunity more effectively than the pharmacologic inhibitor rapamycin. To specifically target activated cells, we conjugated an siRNA targeting the mTORC1 component raptor to an aptamer that binds 4-1BB, a costimulatory molecule that is expressed on CD8+ T cells following TCR stimulation. We found that systemic administration of the 4-1BB aptamer-raptor siRNA to mice downregulated mTORC1 activity in the majority of CD8+ T cells, leading to the generation of a potent memory response that exhibited cytotoxic effector functions and enhanced vaccine-induced protective immunity in tumor-bearing mice. In contrast, while treatment with the general mTORC1 inhibitor rapamycin also enhanced antigen-activated CD8+ T cell persistence, the cytotoxic effector functions of the reactivated memory cells were reduced and the alloreactivity of DCs was diminished. Consistent with the immunological findings, mice treated with rapamycin, but not with 4-1BB aptamer-raptor siRNA, failed to reject a subsequent tumor challenge.